Carrier Transport and I-V Characterization of Si, An/Si and Ag/Si Silicides Using Photoacoustic and Four Point Probe Techniques - Yap, Siew Hong (2005)
The AdSi and Ag/Si systems have been studied extensively due to the importance of carrier transport and I-V characterization of metal silicide compounds in microelectronic applications. In this study, the metal thin film was deposited on the polished Si substrate and annealed in air environment. Open photoacoustic cell and four point probe techques were applied for carrier transport and I-V characterization respectively of Si substrate, AulSi, Ag/Si interface system at room temperature. X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) analysis were used to confirm the silicide formation and sample surface microstructure respectively. The thermal diffusivity and diffusion coefficient of Si substrate were found independent of the surface condition. The surface recombination velocity values for the polished surface were in the range of 392.3 cm/s to 458.0 cm/s and the band to band recombination lifetime for polished surface ranged from 11.57 ps to 17.28 ps. For the annealed Au(150 nm)ln-Si sample, gold silicide clusters were agglomerated out to the sample surface while gold clusters were shrunk. The silicide clusters have caused the surface and bulk recombination process to dominate. Au8 9 and Au7Si (622) silicides were formed on Adp-Si sample after annealing at temperatures of 363 "C and 800 "C respectively. The surface recombination velocity increased from 408.0 cmls to 596.8 crnls as the annealing temperature increased. The surface and bulk recombination process increased with the formation of AqSi silicide, which indicates that Au7Si (622) silicide was present as n-conducting that in contact with the p-Si substrate to form p-n junction characterization (Schottky curve) at the annealing temperature of 800 "C. In this investigation, we found a new approach for the Ag miscible with Si to form the silver silicide compounds for the Aglp-Si system. In the approach, the suitable type of the Si substrate, deposited thin film thickness, annealing temperature and time were the main factors for the chemical reaction within Ag and Si. We also found a transition from 2-D to 3-D growth (Stranski-Krastanov mode) of silver and silver silicide clusters. For AgJp-Si system, the thermal diffusivity was in the range of 0.800 cm2/s to 0.850 cm2/s. The increased surface and bulk recombination process was due to the formation of silver silicide on the sample surface. The I-V characteristic illustrated an ideal diode junction and Schottky curve for annealed Ag(100 nm)/p-Si and annealed Ag(150 nm)/pSi respectively. We suggested that Ag3Si silicide became n-conducting on the p-type Si which responsible in forming Schottky diode junction. The surface recombination velocity and band to band recombination lifetime of annealed Ag(150 nm)/n-Si sample was 428.7 cmls and 8.86 p respectively. Both annealed Agln-Si samples exhibited linear I-V relation in the range of -40 mV to 90 mV.